Diagnosis and management of mild to moderate psoriasis. Issue 7 (4th September 2020) - Le Roux, Emma; Frow, Helen
Abstract : Psoriasis is a common long‐term inflammatory skin condition, which when mild or moderate in severity can be managed effectively with topical treatments and lifestyle advice. This article focuses on the management of mild to moderate psoriasis in primary care.